Lexical Aspects in English Nursery Rhymes for Kindergarten Level - Ika Paramitha Lantu; Oniwo Tiladuru (Sintuwu Maroso Journal of English Teaching, 2019)
This research aims to analyze the lexical aspects in English nursery rhymes at Peniel Kindergarten school. Design of this research is descriptive qualitative. Data are gained by observation, interview and documentations. The result of this research shows that the five lexical aspects that found in English nursery rhymes, they are: repetition, synonymy, antonymy, meronymy and hyponymy.  Repetition type is the most dominant in the English nursery rhymes that are used at Peniel Kindergarten, it gives contribution toward the building of new vocabulary of the children through English nursery rhymes.